(untitled) - Bourne, Russell (Hoboken, N.J., 2006)
Cradle of Violence introduces the maritime workers who ignited the American Revolution: the fishermen desperate to escape impressment by Royal Navy press gangs, the frequently unemployed dockworkers, the wartime veterans and starving widows--all of whose mounting "tumults" led the way to rebellion. These were the hard-pressed but fiercely independent residents of Boston's North and South Ends who rallied around the Liberty Tree on Boston Common, who responded to Samuel Adams's cries against "Tyranny," and whose headstrong actions helped embolden John Hancock to sign the Declaration of Independence. Without the maritime mobs' violent demonstrations against authority, the politicians would not have spurred on to utter their impassioned words; Great Britain would not have been provoked to send forth troops to quell the mob-induced rebellion; the War of Independence would not have happened.
Keywords: Violence,Mobs; History,History; 18th century,18th century; Massachusetts,Boston,Massachusetts,Boston